Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/hiv.12203
|View full text |Cite
|
Sign up to set email alerts
|

Gender inequalities in the response to combination antiretroviral therapy over time: the Swiss HIV Cohort Study

Abstract: ObjectivesGender-specific data on the outcome of combination antiretroviral therapy (cART) are a subject of controversy. We aimed to compare treatment responses between genders in a setting of equal access to cART over a 14-year period. MethodsAnalyses included treatment-naïve participants in the Swiss HIV Cohort Study starting cART between 1998 and 2011 and were restricted to patients infected by heterosexual contacts or injecting drug use, excluding men who have sex with men. ResultsA total of 3925 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…In previous European studies11, 12, 13, 14 of socioeconomic status and ART outcomes in which education level was used as the sole indicator of socioeconomic status, lower education level was associated with virological non-suppression in two of three studies. Two additional European studies considered employment status and noted that unemployment was associated with twice the adjusted risk of virological failure 15 and that viral load of more than 50 copies per mL was associated with twice the unadjusted odds of developing inability to work among those able to work when starting ART 25 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In previous European studies11, 12, 13, 14 of socioeconomic status and ART outcomes in which education level was used as the sole indicator of socioeconomic status, lower education level was associated with virological non-suppression in two of three studies. Two additional European studies considered employment status and noted that unemployment was associated with twice the adjusted risk of virological failure 15 and that viral load of more than 50 copies per mL was associated with twice the unadjusted odds of developing inability to work among those able to work when starting ART 25 .…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, the associations between socioeconomic factors and HIV outcomes in the USA might not be generalisable to settings with free universal health care, which have been little studied 11 . Findings of two large European studies, the Swiss HIV Cohort study 12 and the Spanish CoRIS study, 13 showed that lower education level was associated with increased odds of viral load being higher than 50 copies per mL at 12 months after ART initiation (unadjusted odds ratios of 1·3 and 1·9, respectively); however, the Danish HIV Cohort study 14 noted no clear association. Additionally, in the Italian ICoNA cohort study 15 in individuals who had been taking ART for at least 6 months, unemployment was associated with double the risk of virological failure compared with working full-time.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of clinical studies, assessing ART over a period of at least 48 weeks between 2000 and 2008, found several significant gender-related differences favouring better efficacy in men than in women [53]. The Swiss HIV Cohort study reported on outcomes in 3925 patients, of whom 1941 were women, with access to combination ART over a 14-year period (1998-2011) [22]. Prior to starting ART, women in this cohort study were younger and had higher CD4 cell counts and lower viral loads than men.…”
Section: Gender Differences In Antiretroviral Responsementioning
confidence: 99%
“…Gender-specific factors can also impact on the clinical care of WLWH post-diagnosisaffecting access to and retention in care, management, and the likelihood of achieving and maintaining viral suppression on ART (Table 1) [12,[17][18][19][20][21][22]. In addition to female-specific challenges around reproductive considerations, pregnancy and menopause, women differ from men in body composition and pharmacokinetic (PK) parameters.…”
Section: Introduction and Epidemiology Overviewmentioning
confidence: 99%
See 1 more Smart Citation